Desain Interior Shelter Kopi Kelompok Tani Kopi Manglayang Bandung - Diya Ulhaq, Graziano Rofi; Saryanto, Saryanto (Program Studi Desain Interior Unikom, 2024)
The coffee shelter at the Manglayang Coffee Farmers Group is a facility that facilitates the processing of coffee fruits and beans. The process of processing coffee seeds starts with washing, separating seeds and fruits, peeling, fermentation, drying, roasting, and packing. Processing facilities and equipment will operate more efficiently if organized properly, allowing issues that could affect product quality to be addressed early on. Therefore, optimizing the arrangement, organization, and circulation of processing within the production space is a crucial part of the coffee bean processing process. Optimizing processing facilities in accordance with the sequence of coffee bean processing can yield better quality coffee beans, while preserving the coffee's characteristics from potential damaging issues, thereby ensuring the consistency of both the quantity and quality of the products produced from the coffee shelter and enhancing the quality of the coffee beans. This article describes the recommendations for interior design in the coffee shelter of the Manglayang Coffee Farmers Group in Bandung based on field data findings. It is hoped that the results of this research discussion can be a design reference for coffee farmer groups in Bandung, in particular, and Indonesia, in general.